Improvements in conveyor drying of rockweed and kelp - Matthildur María Guðmundsdóttir 1990- (2014)
The drying industry in Iceland is a rapidly growing industry where new technology has been applied in recent years. Seaweed drying is an energy intensive process which requires considerations regarding the utilization of raw material. For better control of this utilization a mass and energy balance model is created for drying of two different seaweed meal productions; rockweed and kelp. In addition the amount of air that is used is estimated. Temperature and relative humidity are used to analyze the energy usage and airflow in the dryer. It is also important and necessary to see how the rate of drying changes during the process and if operating parameters should be changed. Pressure drop in the process is also used to indicate how air flows through the drying chamber. By applying these methods, improvements in the drying process can be investigated in order to find what is done correctly. The location of temperature and relative humidity sensors in the dryer is examined to determine if it is possible to control the drying based on their readings. In addition the location of the pressure sensor is observed as well as if extra sensors should be installed along with which measurements are worth recording. Þurrkiðnaðurinn á Íslandi er ört vaxandi atvinnugrein þar sem miklar tækninýjungar hafa orðið á síðustu árum. Þurrkun á þörungamjöli er orkufrekt ferli sem krefst þess að hugsað sé út í nýtingu hráefnisins. Til þess að ná aukinni stjórn á nýtingu hráefnis er massa- og orkuvægi sett upp fyrir þurrkun annars vegar á þangi og hins vegar þara. Það er framleiðsla mjöls úr klóþangi og hrossaþara. Að auki er áætlað magn af lofti sem notað er við þurrkunina. Hitastig og hlutfallslegur loftraki loftsins sem notað er til þurrkunar eru notuð til þess að greina orkunotkun og loftflæði í þurrkaranum. Þurrkhraði er notaður til þess að sjá hvernig varan þornar eftir því sem líður á þurrkferlið, en það getur sagt til um það hvernig ferlinu skuli stýrt. Þrýstifall yfir færiböndin er mælt og notað til þess að skoða hvernig loftið ...